Strategi inovasi dan diferensiasi produk sebagai upaya peningkatan daya saing bank syariah - Azizah, Alfia Nur (Maliki Interdisciplinary Journal, 2025)
The rapid growth of the economy today has led to intense competition among companies striving to dominate and maintain their market positions. Every company seeks to expand its market share and sustain its existence amid increasingly fierce competition. This condition also applies to financial institutions, both conventional and Islamic. Islamic banks, in particular, face the challenge of competing not only with conventional banks but also with other Islamic banks in providing the best services and ensuring customer satisfaction. To address these challenges, the implementation of effective and well-directed strategic management is essential. Strategic management plays a crucial role in formulating policy actions that align with the company’s vision and mission while adapting to the dynamic business environment. Each strategic decision must be carefully considered to ensure consistency with the organization’s long-term goals. Errors in decision-making may lead to serious consequences, such as decreased customer loyalty or reduced income. Based on a literature review, it can be concluded that the application of strong and adaptive strategic management is the key to winning market competition. With the right strategy, Islamic banks can strengthen their competitiveness, enhance customer trust, and maintain sustainable growth amid global economic changes.